2021
DOI: 10.1001/jamapsychiatry.2021.1969
|View full text |Cite|
|
Sign up to set email alerts
|

Contingency Management for Patients Receiving Medication for Opioid Use Disorder

Abstract: IMPORTANCE Medication treatment for opioid use disorder (MOUD) is efficacious, but comorbid stimulant use and other behavioral health problems often undermine efficacy.OBJECTIVE To examine the association of contingency management, a behavioral intervention wherein patients receive material incentives contingent on objectively verified behavior change, with end-of-treatment outcomes for these comorbid behavioral problems.DATA SOURCES A systematic search of PubMed, Cochrane CENTRAL, Web of Science, and referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 94 publications
5
60
0
Order By: Relevance
“…Although evidence-based treatment options for other drug use disorders are somewhat limited, contingency management has been found to be an effective treatment strategy for both opioid use disorder and stimulant use disorder. 42 , 43 Polysubstance use can be intentional, but individuals who use drugs are sometimes inadvertently or unknowingly exposed to other drugs, particularly synthetic opioids. The same harm-reduction strategies mentioned earlier, in addition to a low-barrier, safer drug supply 44 and educational efforts that address unintentional opioid exposure, need to be accessible to all homeless-experienced individuals who use drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence-based treatment options for other drug use disorders are somewhat limited, contingency management has been found to be an effective treatment strategy for both opioid use disorder and stimulant use disorder. 42 , 43 Polysubstance use can be intentional, but individuals who use drugs are sometimes inadvertently or unknowingly exposed to other drugs, particularly synthetic opioids. The same harm-reduction strategies mentioned earlier, in addition to a low-barrier, safer drug supply 44 and educational efforts that address unintentional opioid exposure, need to be accessible to all homeless-experienced individuals who use drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Research is also needed to directly assess the impact of MOUD dose and receiving psychosocial treatments on MOUD retention and outcomes among people who use methamphetamine/amphetamines. Randomized controlled trials have found that providing contingency management and cognitive behavioral therapy to patients who used stimulants in MOUD reduced stimulant use, suggesting that offering concurrent, co-located treatments for multiple substance use disorders can benefit patients [ 70 72 ]. While there are currently no FDA-approved medications to treat amphetamine use disorder, ongoing work to advance pharmacologic treatment may also create opportunity for better simultaneous treatment [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…It involves the provision of positive reinforcements, such as money or gift cards, for target behaviors such as drug abstinence. Multiple randomized controlled trials have demonstrated the efficacy of contingency management in reducing methamphetamine use and increasing treatment retention [ 24 27 ]. However, contingency management is not widely available and generally underutilized as a treatment [ 28 ].…”
Section: Introductionmentioning
confidence: 99%